Statement of Problem: Dangerous Desires in Orwell's 1984 and the Present Spanish Penal Code - Alison Hogg (Oñati Socio-Legal Series)
Our construct of a dangerous subject has changed little over the past century. Dangerous subjects in Oceania, a region created by Orwell in his novel 1984 in a constant state of war, consciously or unconsciously manifest too much autonomy. Self-autonomy and agency breach established moral codes of conduct and manifest an inability to self-govern and conform i.e. discipline. What is deemed dangerous is constructed by Ingsoc, Oceania’s prevailing political philosophy; however, if considered of value to the party, time is invested and mandatory treatment is imposed to bring them into line with normative conduct. This treatment consists in stripping them of their identity and desires, which is achieved through them being rendered physically and psychologically innocuous. In the same vein, two new dangerous collectives were designated by the Spanish legislature in a reform introduced to the Penal Code in June 2010, the terrorist and sex offender. On this occasion, it is their efforts to resist this normalization onslaught that renders them dangerous. Unable to incarcerate indeterminately or execute both collectives, a new post-custodial security measure is deployed to ensure that both collectives remain socially and politically isolated. This article compares the dangerous symptomatology depicted by Orwell in 1984 with the dangerous offender constructed by the Spanish legislature in OL 5/2010, the problematization of their habits and behaviours as well as the alleged cure offered to these dangerous subjects. For Ingsoc and the Spanish legislature, the imminent danger is a threat to social and public order.